LabVIEW based Automation Guide for Microwave Measurements - Dubey, Satya Kesh.; Narang, Naina; Negi, P. S.; Ojha, V. N.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The book is focused on measurement automation, specifically using the LabView tool. It explains basic measurements in a simplified manner with appropriate step-by-step explanations and discussions of instrument capabilities. It touches upon aspects of measurement science, microwave measurements and software development for measurement. The book can be used as a guide by technicians, researchers and scientists involved in metrology laboratories to automate measurements. The book explains the development process for automation of measurement systems for every step of the software development lifecycle. It covers system design and automation policy creation. The book uses a top-down approach which enables the reader to relate their own problems and develop a system with their own analysis. The book includes many examples, illustrations, flowcharts, measurement results and screenshots of a worked-out automation software for microwave measurement. The book includes discussions on microwavemeasurements-attenuation, microwave power and E-field strength. The contents of this book will be of interest to students, researchers and scientists working in the field of electromagnetism, antennas, communication and electromagnetic interference/electromagnetic compatibility (EMI/EMC). .
Keywords: Telecommunication; Mathematical physics; Microwaves, RF Engineering and Optical Communications; Theoretical, Mathematical and Computational Physics; Communications Engineering, Networks